Anesthesia Management in Patient with Eclampsia and HELLP Syndrome: A Case Report - Basith, Abd; Adnan, Muhammad Luthfi (Universitas Wijaya Kusuma Surabaya, 2026)
Background: Eclampsia and HELLP Syndrome is one of the emergency that occurs in pregnant women and is one of the causes of death in pregnant women and fetus. It can be a challenge for an anesthesiologist for anesthetic management during and after pregnancy termination. Objective: This report presents anesthetic management using combination propofol, rocuronium, and fentanyl in cases of eclampsia with HELLP syndrome and monitoring during pregnancy termination surgery. Case Presentation: A 24-year-old female patient with a gestation age of 36 weeks came to the emergency room with seizure. During the latest antenatal care found high blood pressure (160/100 mmHg). Based physical and laboratory findings the patients diagnosed eclampsia and HELLP syndrome. The patient was given general anesthesia with induction of propofol 2 mg/kg with a rapid bolus, rocuronium 1 mg/kg IV, and fentanyl 2 mcg/kg with endotracheal intubation. During surgery, the patient was hemodynamically stable and the baby was born with an Apgar score of 9/10. The patient was admitted to the ICU for vital signs monitoring for 4 days before being discharged after the sixth day. Result: Patients with eclampsia and HELLP syndrome require careful anesthetic management because it not only impacts maternal condition, but also the outcome of the neonates. Conclusion: This condition required special treatment including by anesthesiologists. Treatment includes how to deal with seizures, the choice of anesthesia technique, prevention of seizures and intraoperative fluids management and ensuring safety for both the mother and the fetus. Lot of controversies with regard to fluid management and monitoring still remain unanswered.